2020
DOI: 10.1001/jamaoto.2020.1585
|View full text |Cite
|
Sign up to set email alerts
|

Hearing and Quality-of-Life Outcomes After Cochlear Implantation in Adult Hearing Aid Users 65 Years or Older

Abstract: for the CI532 Study Group IMPORTANCE Hearing loss, especially moderate to severe forms, has the potential to negatively affect an individual's physical, social, emotional, and cognitive well-being. Moreover, having ineffective binaural hearing increases difficulty understanding speech in noise and leads to a greater degree of social isolation and loneliness and a reduced quality of life (QoL).OBJECTIVE To explore the audiometric and holistic effects of cochlear implantation in a group of adults 65 years or old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 44 publications
5
39
1
Order By: Relevance
“…Cochlear implantation is an effective treatment option across the lifespan for patients with moderate‐to‐profound sensorineural hearing loss (SNHL) and limited speech recognition with appropriately fit hearing aids 1–11 . Cochlear implant (CI) recipients demonstrate significant improvements in speech recognition within the initial months of device use, 9,12 though a wide variability in performance is observed 13–16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cochlear implantation is an effective treatment option across the lifespan for patients with moderate‐to‐profound sensorineural hearing loss (SNHL) and limited speech recognition with appropriately fit hearing aids 1–11 . Cochlear implant (CI) recipients demonstrate significant improvements in speech recognition within the initial months of device use, 9,12 though a wide variability in performance is observed 13–16 .…”
Section: Introductionmentioning
confidence: 99%
“…Cochlear implantation is an effective treatment option across the lifespan for patients with moderate-toprofound sensorineural hearing loss (SNHL) and limited speech recognition with appropriately fit hearing aids. [1][2][3][4][5][6][7][8][9][10][11] Cochlear implant (CI) recipients demonstrate significant improvements in speech recognition within the initial months of device use, 9,12 though a wide variability in performance is observed. [13][14][15][16] Factors observed to influence the variability in speech recognition within the initial months of CI use include preoperative acoustic hearing, 17 duration of severe-to-profound SNHL, 12,13,[15][16][17][18][19][20] and age at implantation.…”
Section: Introductionmentioning
confidence: 99%
“…These patients, with a pre-operative AI-PAC ≥ 4.2%, showed better monosyllabic word recognition than those with a lower AI-PAC. Nevertheless, monosyllabic word recognition was poorer than expected for 6-months follow-up examination in both groups 31 33 .…”
Section: Discussionmentioning
confidence: 55%
“…It is thought that it can directly affect the health of the person while participating more fully in daily life activities. In a multicentric study, it has been shown that the CI applied to adults over the age of 65 significantly benefits hearing and quality of life and can facilitate the concept of healthy aging [ 69 ]. Consequently, CI surgery was thought to be the most effective solution for our patients.…”
Section: Discussionmentioning
confidence: 99%